Evolutionism and genetic psychology in Lithuania (end of 19th century to the beginning of 20th century) - Gučas, A. (Psichologija, 1962)
At the end of 19th century, in the process of popularization of the natural sciences, a number of progressive Lithuanian publicists, writers, young scientists took part (J. Šliupas, J. Adomaitis-Šernas, S. Matulaitis, J. Biliūnas, J. Mikolainis, and others). They spread the ideas about the eternity and shift of substance, evolution of the organized matter from the inanimate nature. In their works they analyze the problem of the origins of the psyche, the anthropogenesis issue, and regularities of children psychic development considering the peculiarities of their age, the content and methods of their upbringing. The substance development matter is closely related to the problem of the origin of the psyche, which was regarded as a function of brain. Psychic cognitive processes were seen as a reflection of natural and social phenomena, the reflection mechanisms were explained from the associative position. Matters of substance evolution inevitably led to the problem of anthropogenesis. J. Adomaitis-Šernas, J. Šliupas and others explained the appearance of new species and their further development by adjustment of the living organisms to environmental conditions. The appearance of people was explained by them as the result of the impact of the surrounding environment on the vital organs of their ancestors. Animals adapt to their surroundings by altering their biological qualities, and people – by developing their sense-organs, mental and other abilities. It was emphasized that improvement of touch along with the capability to use hands played a major role for the appearance and development of the human psyche. Among other traits distinguishing humans and animals, language, emotions, and creative activity were indicated. However, the above mentioned authors did not generalize or reveal the qualitative differences between a man and animal. Therefore, anthropomorphic outlooks are clearly expressed in the 20th century works of Lithuanian publicists. Even the authors close to Marxism J. Biliūnas and S. Matulaitis failed to escape such error. The matter of the origin of consciousness has not been thoroughly analyzed, but many studies reiterated the idea that a man at the beginning of his conscious development failed to perceive his own subjective world. P. Mikolainis wrote that the primitive man “contemplated without realizing that he is contemplating”. At the end of 19th century the problem of the appearance of human consciousness was approached, but it became the object of investigation only in later works of P. Bytautas and Vydūnas. At the end of 19th century the disclosure of key laws of the development of human psyche was particularly addressed in search for more successful solution of education problems. A big influence was made by the psychological and pedagogical attitudes of Spencer. To prove that the nature of the human psyche was not supernatural, it was not enough to just state that human psyche undergoes changes because its organ – the nervous system – changes. J. Adomaitis-Šernas, J. Šliupas, P. Mikolainis and others sought proof in the psychic activity of primitive nations, mental development of children and adults having inferior sense-organs, normal children developing in different conditions. Heated polemics was held with the clerical trend authors who did not acknowledge the development of human moral qualities and grounded their point of view on supposed steadfastness of human nature. Capitalist order was condemned, depriving workers’ children of full development of their abilities. The outlook was progressive but rather narrow-minded because the mental development was viewed as the outcome of mechanical impact of outer conditions, as a process occurring without inner conflicts and contradictions. As for mental evolution, it was maintained that “gradual alteration of spiritual qualities” is taking place (J. Šliūpas) which progresses from the lowest stages to the upper ones. J. Adomaitis-Šernas concluded a list of periods of the progress of the human psyche, including the senility. Acknowledgement of the development stages had influence on the theory of upbringing; it was required to harmonize learning and upbringing with the properties characteristic to children’s age. Furthermore, an idea of actual education was brought forward by emphasizing the necessity to teach children things necessary for life. However, such requirements held conceited threat to choose the pragmatic way in the theory of pedagogy.